Two Faces of Grassland: A Comparative Study on the Impact of Tourism Development Model on Grassland Environment - Jing Wang; Shu-Chen Tsai (Engineering Proceedings)
With the boom in outdoor recreational activities in Inner Mongolia, grassland protection has become significant, but the impact of different tourism models on the grassland environment has received little attention. The purpose of this study was to explain the impact of different tourism development models on the grassland environment from a local perspective through small-scale case studies. We took two types of grasslands as objects: the scenic grassland led by developers and the natural grassland led by herdsmen. The study results showed the following: (1) there are four types of tourism development models in the research area; (2) three factors that affect model development are physical geography, seasonality, and policy; and (3) herders emphasized the risks of grassland under climate change. Finally, the main factor that divides the grassland into two appearances is the formalization of tourism content. The concentration of livestock impacts the tourism model. The optimized tourism model was small-scale grassland ecotourism, which best integrated culture and development potential.